The Mediating Effect of Communication on the Relationship Between Leadership Style and Employee Commitment - Al Raeesi, Ali Murad Ali Al Taher; Norsamsinar Samsudin (European Journal of Multidisciplinary Studies, 2020)
This study investigates the relationship between leadership style, and employees’ commitment among Dubai government servants. The main objective of this study is to determine the relationship between leadership styles and employees’ commitment at Dubai Immigration Department (DID). The study also aims to examine the mediating effects of communication in the relationship between leadership styles and employees’ commitment in DID. The target population of this study is 6000 employees working in DID. Thus, the sample size will be approximately 361. This research will use simple random sampling techniques.